Implementasi n-Gram Technique Dalam Deteksi Plagiarism Pada Tugas Mahasiswa - Lisangan, Erick Alfons (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2013)
Student’s assignment is one of component in the course assessment. The problem that can be found is a student copied the work of another student or can be called plagiarism. There are several ways to detect plagiarism based on similarity text, such as n-gram technique. In this research, Sorensen-Dice Coefficient is used to get the percentage of similarity text between the documents of student’s assignment and detection of plagiarism limited to text documents. N values that used in this research are 3, 4, 5, 6, 7 and obtained best N value is 7 based on the average of difference relevance